Neurological Damage by Coronaviruses: A Catastrophe in the Queue! - Mishra, Ritu; Banerjea, Akhil C. (Frontiers in Immunology, 2020)
Neurological disorders caused by neuroviral infections are an obvious pathogenic manifestation. However, non-neurotropic viruses or peripheral viral infections pose an actual challenge as their neuropathological manifestations do not emerge because of primary infection. Their secondary or bystander pathologies develop much later like a syndrome during and after the recovery of patients from the primary disease. Massive inflammation caused by peripheral viral infections can trigger multiple neurological anomalies. These neurological damages may include a general cognitive and motor dysfunction upto a wide spectrum of CNS anomalies such as Acute Necrotizing Haemorrhagic Encephalopathy, Guillain-Barré syndrome, Encephalitis, Meningitis, anxiety and other audio-visual disabilities. Peripheral viruses like Measles virus, Enteroviruses, Influenza viruses (HIN1 series), SARS-CoV-1, MERS-CoV and recently emerged SARS-CoV-2 are reported to cause various neurological manifestations in patient and proven to be neuropathogenic even in cellular and animal model systems. This review presents a comprehensive picture of CNS susceptibilities towards these peripheral viral infections and explains some common underlying themes of their neuropathology in human brain.